Cyclic self dual codes of length pq over Z4. (17th November 2022) - Jain, Sonal; Batra, Sudhir
Abstract: Explicit expressions for primitive idempotent in the ring are obtained, where p and q are distinct odd primes with multiplicative order of 2 modulo p and modulo q being and ϕ ( q ) respectively. Hence the idempotent generators of cyclic self dual codes of length pq over Z 4 are obtained. Further, it is observed that when p = 8 k - 1 and q = 8 m - 3, the extension of each of these self dual codes augmented with all-ones vector is a Type I code.